Pengelolaan Penerimaan Peserta Didik Baru (Ppdb) Pada Smp Negeri 2 Wonogiri - Sudrajat, Untung; , Dr. Suwaji, M.Kes; , Dr. Suyatmini, M.Si (2015)
The purpose of this study: 1) Describe the dissemination plan, 2) Describe the target setting, 3) Describe the socialization of school excellence, 4) Responding to concerns related to the school community paradigm shift from public school to school-based Islamic. Research location in SMP Negeri 2 Wonogiri. This type of research is qualitative research. Data collection techniques using observation, interviews, and document analysis method. Planning begins from the formation of the committee and the program plan. Results of research on management efforts acceptance of new students in Junior High School 2 Wonogiri is as follows: 1. Management Procedures admission of new students to the school to plan socialization purposes, 2. Attempts setting a target to be achieved. 3. Efforts to socialize school excellence. 4. Efforts to form a moral and noble character is the local addition to religion classes, additional hours of religion and the addition of religious laboratories and increase the number of teachers who stratum 2 (S2). Keywords: management, reception Learners, Junior High School